Aggregation technology of common goods and its strategic consequences: Global warming, biodiversity, and siting conflicts - Katharina Holzinger (Max-Planck-Projektgruppe Recht der Gemeinschaftsgüter, 2000)
The analysis of common goods needs to look very carefully at the characteristics of the goods and of the social situations of their provision. Different characteristics lead to different strategic constellations and therefore to different opportunities for institutional solutions to the problems of provision. Basic differences in strategic constellations can be shown clearly by employing matrix games. In this paper a particular attribute of common goods, their aggregation technology, is systematically analyzed. Variations in this dimension are exemplified by three cases from environmental policy: global warming, biodiversity, and siting conflicts. It becomes clear that the analysis of one specific attribute of a good will seldom suffice to predict empirical behavior. Nevertheless, rigorous game theoretic analysis provides valuable insights into the links between the characteristics of common goods and the need for institutions
Keywords: 330; Gemeingüter; Öffentliche Güter; Neue politische Ökonomie; Spieltheorie; Klimaschutz; Artenvielfalt; Lokale öffentliche Güter; Externer Effekt; Standortwahl; Theorie